Pemberdayaan Keluarga Sebagai Upaya Meningkatkan Kesehatan Lansia - Aris Wawomeo; Sisilia Leny Cahyani; Raimunda Woga; Theresia Avila Kurnia (Utan Kayu Publishing, 2023)
The increasing life expectancy in Indonesia is a sign that the government must be more serious in improving programs related to the elderly, especially the health of the elderly in a comprehensive manner so that the welfare of the elderly is getting better and they can live properly. Family support is needed to maintain the health of the elderly, to improve the quality of life of the elderly. The main health problem experienced by the elderly population worldwide is non-communicable diseases. The targets of this community service activity are posyandu cadres and families who have the elderly. This type of activity is community service in the form of health education related to elderly health problems, providing training to families, filling out the Family Health Monitor board and the